"The Silence of the Dead": Remembering Suicide Victims and Reimagining the Communion of Saints. (June 2020) - Antus, Elizabeth L.
Though the Catholic Church has become more mindful of the role that mental illness, especially depression, often plays in suicide, this greater awareness needs development so that Catholic theology can de-stigmatize suicidal people without normalizing suicide. To this end, the article draws upon recent psychological work on suicide to highlight the deep suffering of suicidal people and to indicate that they are, generally, victims of severe mental illness. Furthermore, attention is drawn to a group who is especially stigmatized: those who have already died by suicide. In response, Johann Baptist Metz's emphasis on anamnestic solidarity with the dead provides an important corrective to this forgetting. Lastly, this revised understanding of suicide decedents helps Catholics develop the doctrine of the communion of saints for today.